Effects of dietary curcumin supplementation on the liver health of juvenile channel catfish (Ictalurus punctatus) fed high-starch diet - Qisheng Lu; Yutong Zheng; Yu Wang; Yulong Liu; Jingyue Cao; Haokun Liu; Junyan Jin; Zhimin Zhang; Yunxia Yang; Xiaoming Zhu; Shouqi Xie; Dong Han (Aquaculture Reports, 2025)
High-carbohydrate diet (HCD) usually leads to metabolic disorders and damages liver health in aquatic animals. Curcumin has been shown to improve antioxidant, hypoglycemic, and hypolipidemic effects. However, whether curcumin helps to ameliorate HCD-induced liver damage in fish remains unknown. Here, we formulated four diets: normal-carbohydrate diet (CON), high-starch diets (HSD), 0.02 % and 0.04 % curcumin added to HSD (HSC0.02 % and HSC0.04 %) to investigate the effects of curcumin on the liver health of channel catfish (Ictalurus punctatus). The results showed that HSC0.02 % or HSC0.04 % treatments had no effect on growth performance and HSC0.02 % treatment showed the best hypoglycemic and hypolipidemic effects compared to the HSD group. Dietary curcumin activated Keap1/Nrf2 to increase hepatic antioxidant capacity (T-AOC, SOD and GSH-PX) and inhibit apoptosis pathway (Bax, Bcl2, Caspase 3 and Caspase 9) (P < 0.05). Importantly, curcumin reduces HSD-induced abnormalities of pentose phosphate pathway (PPP), triglyceride and cholesterol synthesis by inhibiting carbohydrate-responsive element-binding protein (ChREBP) expression (P < 0.05). Thus, we elucidated that curcumin ameliorates HSD-induced metabolic dysfunction and damage by inhibiting ChREBP signaling in channel catfish and assessed the feasibility of curcumin as an aquafeed additive to improve liver health in aquatic animals.